Russian Federation : Financial Sector Assessment Program: Detailed Assessment of Observance Basel Core Principles for Effective Banking Supervision (BCP). (IMF Staff Country Reports; Country Report ;, 2016)
This paper evaluates observance of the Basel Core Principles for Effective Banking Supervision in the Russian Federation. The legal framework currently in place provides the Central Bank of Russia (CBR) with necessary powers and responsibilities. The CBR may authorize banks, conduct ongoing supervision, oversee compliance with laws, and undertake corrective action to address safety and soundness. Major new reforms increase many aspects of the CBR's duties and powers, although implementation has not yet been tested in all cases. The Russian licensing regime for banks appears exhaustive. However, the legal regime for major acquisitions was found to be weak.